RELASI SOSIAL ANTAR PEDAGANG PEREMPUAN DI PASAR TRADISIONAL DAHLIA SUNGAI JAWI PONTIANAK - Yuyun, Melina; Bahari, Yohanes; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrackThis research was to find out the from of associative and dissociative social relations between female traders in traditional markets dahlia sungai jawi Pontianak. This research method was descriptive with a qualitative approach. The source of data of this research was the female traders in the traditional market of dahlia Sungai Jawi Pontianak and the data was a data sheet provided by the office of UKM trade of Pontianak and the results of interviews with female traders in the traditional market of Dahlia Sungai Jawi Pontianak. The results showed that associative social relations in the from of bargaing among fellow female traders in the traditional market of dahlia Sungai Jawi Pontianak did not have any agreement between fellow traders and the from of exchange of goods and services in the from of many exchange. Assosiative social relations in the from of harmony could be seen, namely guarding the stalls of fellow traders, and helping to sell the merchandise among fellow traders. Dissosiative social relations in the from of economic competition was seen among fellow femaletraders in the traditional market of dahlua namely,competition of the quality of the new trade, competition for complete the merchandise, and competition of service. Â Keywords :Female Trader, Froms of Relations , Social Relations